Disrupted Balance of MMPs/TIMPs in Gastric Carcinogenesis–Paradoxical Low MMP-2 Expression in Tumor and Stromal Compartments as a Potential Marker of Unfavorable Outcome. (9th August 2015) - Donizy, Piotr; Rudno-Rudzinska, Julia; Kaczorowski, Maciej; Kabarowski, Jedrzej; Frejlich, Ewelina; Kielan, Wojciech; Matkowski, Rafal; Halon, Agnieszka
<x xml:space="preserve">Abstract</x> The aim of the study was to find correlations between MMP/TIMP reactivity and the expression of angiogenic factors, and relationships between these parameters and clinicopathological features of gastric cancer patients. Receiver Operating Characteristic curve analysis was used to find cut-off points that enabled fair decision-making in survival analysis. Low levels of MMP-2 expression in tumor and stromal compartments were significantly associated with poor prognosis–the probability that a patient would die within 60 months of surgery if their MMP-2 was low, and was about 0.8 in both neoplastic and stromal compartments.